2018
DOI: 10.7150/ijms.23150
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Adaptations Induced by Resistance Training in Animal Models

Abstract: In the last 10 years the number of studies showing the benefits of resistance training (RT) to the cardiovascular system, have grown. In comparison to aerobic training, RT-induced favorable adaptations to the cardiovascular system have been ignored for many years, thus the mechanisms of the RT-induced cardiovascular adaptations are still uncovered. The lack of animal models with comparable protocols to the RT performed by humans hampers the knowledge. We have used squat-exercise model, which is widely used by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 76 publications
1
15
0
1
Order By: Relevance
“…A model to assess the benefits of resistive training. Briefly, for this method, the animal is suspended and positioned on its hind legs, then electrical stimulation coerces the muscle to flex and the animal squats against a weight [ 165 , 166 ]. All have their advantages and disadvantages (as reviewed by Feng et al (2019)), but they have allowed researchers to study the molecular benefits of exercise.…”
Section: Physiological Stimulators Of Hydrogen Sulfide Productionmentioning
confidence: 99%
“…A model to assess the benefits of resistive training. Briefly, for this method, the animal is suspended and positioned on its hind legs, then electrical stimulation coerces the muscle to flex and the animal squats against a weight [ 165 , 166 ]. All have their advantages and disadvantages (as reviewed by Feng et al (2019)), but they have allowed researchers to study the molecular benefits of exercise.…”
Section: Physiological Stimulators Of Hydrogen Sulfide Productionmentioning
confidence: 99%
“…This response is attenuated in trained athletes during exercises [21]. The impact of resistance training on cardiovascular function was outlined in recent studies, with positive effects on blood pressure noted at rest [22], although the underlying mechanisms for this remain under investigation [23]. One study [24] found that the pyramidal method specifically reduced blood viscosity, thereby diminishing cardiovascular risk factors.…”
Section: Cardiovascular Adaptationsmentioning
confidence: 99%
“…esistance training is associated with various adaptations in the organs of the body [1]. However, functional adaptation and morphology can be reduced after a short R period of detraining [2].…”
Section: Introductionmentioning
confidence: 99%